Improving the Enrichment of Submicron-Sized Particles by Size Decreasing of Cruciform Cross-Sectional Microchannel in Viscoelastic Microfluidics - Jaekyeong Jang; Eunjin Kim; Sungdong Kim; Ok-Chan Jeong; Sangwook Lee; Younghak Cho (Biosensors)
The manipulation of cells and bioparticles has garnered significant interest in the field of viscoelastic microfluidics, particularly regarding its capacity for single-stream focusing within a three-dimensional and simple microchannel structure. The inherent simplicity of this method enables the effective manipulation of particles, facilitating the separation and focusing of various cell types, including blood cells, circulating tumor cells (CTCs), and microalgae. However, the viscoelastic nature of the particles imposes limitations in the handling of submicron-sized particles, due to a significant decrease in the viscoelastic force acting on the particle. In this study, we propose a microfluidic device featuring a cruciform cross-sectional microchannel with 45 µm and 45 µm of its vertical and horizontal size, respectively. The cruciform microchannel, which has a 270° reflex angle on four corners, can increase the viscoelastic force on the particles, allowing the device to focus submicron-sized particles down to 180 nm in a single-stream manner. It is important to note that the single-stream formation was maintained, while the channel width at the outlet region was drastically increased, allowing for the enrichment of submicron-sized particles. For biological feasibility, the proposed device also demonstrates the single-stream focusing on biological particles such as bacteria. The presented microfluidic device would have great potential for the focusing and enrichment of nanoparticles including bacteria in a highly robust manner, expecting its use in the various fields such as diverse biological analysis and biomedical research.